Risk factors for symptomatic rotator cuff tears: a retrospective case–control study - Zhao, Jinlong; Zeng, Lingfeng; Liang, Guihong; Luo, Minghui; Yang, Weiyi; Liu, Jun; Pan, Jianke (Frontiers in Medicine, 2024)
Background: The incidence and diagnostic rate of rotator cuff tears (RCTs) have increased significantly. The purpose of this study was to investigate and analyze the risk factors for symptomatic RCTs to provide a basis for their prevention and treatment. Methods: We retrospectively analyzed the relevant clinical indicators of 193 randomized clinical trial (RCT) patients and 161 non-RCT patients hospitalized with shoulder pain as the main complaint from January 1, 2017, to August 31, 2021. Univariate analysis and multivariate logistic regression analysis were used to analyze the differences in potential risk factors between the two groups. Results: Univariate analysis revealed that age (P < 0.001), body mass index (BMI) (P = 0.036), hypertension (P < 0.001), coronary heart disease (P = 0.028), history of shoulder trauma (P < 0.001), hyperlipidemia (P = 0.025), type III acromion (P = 0.012) and critical shoulder angle (CSA) (P < 0.001) increased the risk of RCTs. Multivariate logistic regression analysis revealed that age ≥ 60 years (OR = 2.61, 95% CI = 1.23 to 5.12), CSA ≥ 35° (OR = 4.24, 95% CI = 1.60 to 11.22), hypertension (OR = 2.34, 95% CI = 1.33 to 4.11) and history of shoulder trauma (OR = 5.20, 95% CI = 2.87 to 9.45) were independent risk factors for symptomatic RCTs. Conclusion: The results of this study showed that age ≥60 years, CSA ≥35°, hypertension and history of shoulder trauma are independent risk factors for symptomatic RCTs and can provide directions for further development of prevention and treatment strategies. Future studies need to clarify the mechanism underlying the association between these risk factors and symptomatic RCTs.